设y=e-2x,则y’等于______.
A: 2e-2x
B: e-2x
C: -2e-2x
D: -2e2x
A: 2e-2x
B: e-2x
C: -2e-2x
D: -2e2x
举一反三
- 设y=e-2x,则y’等于______. A: 2e-2x B: e-2x C: -2e-2x D: -2e2x
- 已知\( y = {x^2}{e^{ - x}} \),则\( y'' \)为( ). A: \( 2{e^{ - x}} - 4x{e^{ - x}} - {x^2}{e^{ - x}} \) B: \( 2{e^{ - x}} - 4x{e^{ - x}} + {x^2}{e^{ - x}} \) C: 0 D: \( 2{e^{ - x}} - 4x{e^{ - x}} \)
- 设 (X, Y) 为二维随机变量,则随机变量ξ = X + Y 与η = X − Y 不相关的充分必要条件为() A: E(X<sup>2</sup>) −[E(X)]<sup>2</sup>= E(Y<sup>2</sup>) −[E(Y)]<sup>2</sup>; B: E(X<sup>2</sup>) = E(Y<sup>2</sup>); C: E(X) = E(Y); D: E(X<sup >2</sup>) + [E(X)]<sup >2</sup>= E(Y<sup >2</sup>) + [E(Y)]<sup >2</sup>.
- 方程$(x^2+1)(y^2-1) + xy y' = 0$的通解为 A: $y^2 = C \frac{e^{-x^2}}{x^2}$ B: $y = C \frac{e^{-x^2}}{x^2}$ C: $y^2 = C \frac{e^{-x^2}}{x^2}+1$ D: $y=C \frac{e^{-x^2}}{x^2}+1$
- 设X,Y为随机变量,E(X)=E(Y)=1,Cov(X,Y)=2,则E(2XY)= A: -6 B: -2 C: 2 D: 6